Agrarian Policies In The Third World: Comparative Study - Chau, Le (1974)
This article compares the fundamental principles of agrarian policies in different countries to understand their performance and why they don´t work in developing countries. The theoretical confusion leads to the application of inadequate production models, not suitable for the reality of most developing countries.